Review of Classification and Regression Classification and Regression Trees (CART) - Díaz Sepúlveda, Juan Felipe; Díaz Sepúlveda, Juan Felipe; Díaz Sepúlveda, Juan Felipe (Corporación Universitaria Americana, 2011)
Depending on the problem, the basic purpose of a classification study may be to produce a correct classificationor predictive discovering the structure of the problem If our goal is the latter, then we are trying to understand whatvariables or interactions of variables describing the phenomenon, that is, give simple characterizations of the conditionsthat determine when an object is In a class more than another. The Classification and Regression Trees,Classification and Regression English Trees (CART), owes its development to L Breiman, J. Friedman, R. Olshenand C Stone, who wrote the book of the same name, published in 1984 [Breiman et al, 1984]. The aim of this paperis to report from the theoretical point of view it is this classification technique.